2020
DOI: 10.1039/d0ra04395h
|View full text |Cite
|
Sign up to set email alerts
|

Targeting severe acute respiratory syndrome-coronavirus (SARS-CoV-1) with structurally diverse inhibitors: a comprehensive review

Abstract: Since the coronaviruses that cause COVID-19 and SARS-CoV-1 share 80% structural similarity, we present a comprehensive review of the diverse molecular inhibitors of SARS-CoV-1. This will help to accelerate drug discovery for deadly coronavirus diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 115 publications
0
16
0
Order By: Relevance
“…HIS:41 and CYS:145 have been known as essential residues during MPro enzymatic activity (Tahir ul Qamar et al, 2020). Inhibiting these residues has a promising effect on preventing virus replication and prevent viral spreading throughout the tissues (Ahkam et al, 2020;Gyebi et al, 2020;Hosseini-Zare et al, 2020;Tahir ul Qamar et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…HIS:41 and CYS:145 have been known as essential residues during MPro enzymatic activity (Tahir ul Qamar et al, 2020). Inhibiting these residues has a promising effect on preventing virus replication and prevent viral spreading throughout the tissues (Ahkam et al, 2020;Gyebi et al, 2020;Hosseini-Zare et al, 2020;Tahir ul Qamar et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Replication of SARS-CoV-2 depends on PLpro and Mpro functions. Inhibitors of SARS-CoV PLpro, in several studies, have been shown to be as effective against SARS-CoV-2 PLpro [44, 45]. Although many of the findings were promising, the development in introducing effective drugs is lagging.…”
Section: Discussionmentioning
confidence: 99%
“…Substrates of 3CLpro are peptides, and therefore peptidic inhibitors derived from the substrates have been developed against 3CLpro [67] . To enhance the binding affinity of peptidic inhibitors to 3CLpro, amino acids of the substrate were substituted to fit the binding pocket perfectly.…”
Section: Inhibiting the Viral Genome Replicationmentioning
confidence: 99%